Resilience in the face of flash floods, landslides and mudflows: the experience of tourist spots in Cameron Highlands - Fauziah Che Leh (Tanjung Malim, 2021)
Resilience in the face of flash floods, landslides and mudflows: the experience of tourist spots in Cameron Highlands by Fauziah Che Leh